Impact analysis of time synchronization error in airborne target tracking using a heterogeneous sensor network - Lee, Seokwon; Yuan, Zongjian; Petrunin, Ivan; Shin, Hyo-Sang (MDPI, 2024)
This paper investigates the influence of time synchronization on sensor fusion and target tracking. As a benchmark, we design a target tracking system based on track-to-track fusion architecture. Heterogeneous sensors detect targets and transmit measurements through a communication network, while local tracking and track fusion are performed in the fusion center to integrate measurements from these sensors into a fused track. The time synchronization error is mathematically modeled, and local time is biased from the reference clock during the holdover phase. The influence of the time synchronization error on target tracking system components such as local association, filtering, and track fusion is discussed. The results demonstrate that an increase in the time synchronization error leads to deteriorating association and filtering performance. In addition, the results of the simulation study validate the impact of the time synchronization error on the sensor network.
Keywords: time synchronization; sensor fusion; track-to-track fusion; target tracking; counter-UAS (CUAS)